2021
DOI: 10.3390/antiox10040523
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly Pea Flower (Clitoria ternatea Linn.) Extract Ameliorates Cardiovascular Dysfunction and Oxidative Stress in Nitric Oxide-Deficient Hypertensive Rats

Abstract: In this study, we examine whether Clitoria ternatea Linn. (CT) can prevent Nω-nitro-L-arginine methyl ester hydrochloride (L-NAME)-induced cardiac and vascular dysfunction in rats. Male Sprague Dawley rats were given L-NAME (40 mg/kg, drinking water) and orally administered with CT extract (300 mg/kg/day) or lisinopril (2.5 mg/kg/day) for 5 weeks. The main phytochemical components of the CT extract were found to be flavonoids. The CT extract alleviated the high blood pressure in rats receiving L-NAME. Decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
2
17
0
4
Order By: Relevance
“…The link between ROS production and RAS activation has been demonstrated in rats treated with l -NAME, where eNOS uncoupling has been demonstrated as a major source of superoxide production. 49 It has been found that NO-deficient hypertensive rats have low levels of antioxidant enzymes, including superoxide dismutase and catalase. 31 Polyphenols are involved in providing fortification against diabetes, cardiovascular, and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The link between ROS production and RAS activation has been demonstrated in rats treated with l -NAME, where eNOS uncoupling has been demonstrated as a major source of superoxide production. 49 It has been found that NO-deficient hypertensive rats have low levels of antioxidant enzymes, including superoxide dismutase and catalase. 31 Polyphenols are involved in providing fortification against diabetes, cardiovascular, and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic nerve overactivity was observed as the contractile response to EFS was increased, but not to exogenous NE in the hypertensive group. An increased sympathetic nerve-mediated contractile response in the mesenteric vascular bed has been observed in L-NAME rats [ 7 ]. This was supported by the evidence that increased central sympathetic drive is the important mechanism contributing to the hypertension induced by chronic inhibition of NOS with L-NAME [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of NO by Nω-nitro-L-arginine methyl ester (L-NAME), a non-specific nitric oxide synthase (NOS) inhibitor, has been established as a treatment to induce [3]. It has been reported that long-term treatment with L-NAME causes sustained hypertension, cardiovascular dysfunction, and remodeling in animals [4][5][6][7]. Moreover, sympathetic nerve-mediated contractile responses are enhanced in the vasculature isolated from NOS inhibitor-treated rats, which is relevant to a high level of plasma norepinephrine and a low level of plasma NO in these animal models [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…3,16 Bunga telang memiliki kandungan fitokimia saponin, tannin, alkaloid, glycoside, phytosterol, karbohidrat, ternatin, flavonoid, resin, anthocyanin, triterpenoid, saponin, phenol, dan anthraquinone. 3,16,17 Hasil analisis fitokimia secara kualitatif pada penelitian Thakur et al (2018) menunjukkan bahwa ekstrak daun telang mengandung protein, karbohidrat, resin, tannin, saponin, flavonoid, alkaloid, steroid, dan glycoside. 18 Antioksidan pada tanaman berfungsi untuk melindungi sel-sel tanaman dari kerusakan akibat cahaya tinggi, melalui penyerapan sinar ultraviolet biru-hijau yang akan menghasilkan spesies oksigen reaktif, juga dikenal sebagai ROS (reactive oxygen species).…”
Section: Pharmaceuticalunclassified